Avaliação de um sistema de filtro domiciliar como estratégia para desfluoretação de água em uma zona rural endêmica para fluorose dentária em Minas Gerais, Brasil - Andreia Maria Araujo Drummond (2013)
OBJECTIVES: High fluoride concentration is found naturally worldwide in water. This study evaluated if a new domestic defluoridation filter system, based on adsorbents microspheres of activated alumina-coal composite, is effective to reduce high fluoride concentrations in an endemic dental fluorosis area. METHODS: A community intervention study was conducted during 22 weeks in 4 houses with 20 individuals, between children, adolescents and adults, in an endemic dental fluorosis rural area in Brazil, where drinking water concentration was 3.7 higher the optimum for the region. During 15 weeks, samples of tap (control) and filtered water were collected 9 times and total daily urine samples were collected 8 times. After this period, one house was replaced in the study due to the interruption of water supply in that specific house. In the subsequent 7 weeks, samples of filtered water were collected 10 times and total daily urine samples, 4 times. Fluoride concentration in water and urine was determined with ion specific electrode. RESULTS: Natural fluoride concentration found in the water was 2.56 ppm (ranging from 2.17 to 2.98). The concentration of fluoride in the filtered water from the system was significantly reduced during the first 5 to 9 weeks of defluoridation (p<0.001). It was found correlation between the concentration of fluoride in urine and filtered water (r=0.31; p=0.003). The system produced a reduction in the concentration of fluoride less than 1.5 ppm over a period of 5 to 9 weeks. The fluoride concentration in the urine of the children did not differ significantly from an adolescent/adult. CONCLUSIONS: The domestic filter developed is effective to reduce the naturally high fluoride concentration in water, proving the system to be an appropriate strategy to provide appropriate water to a community in an endemic dental fluorosis area, but the longevity of the system should be further studied.